Desert Bugs (Hemiptera: Heteroptera: Thaumastellidae): New records and review of the distribution and habitat of this relict group - Kment, Petr; Jacobs, Dawid H.; Carapezza, Attilio; Deckert, Jürgen; Rider, David A.; Kóbor, Péter (Zootaxa, 2024)
The known distribution and habitat information of the three described species of the genus Thaumastella Horváth, 1896 (Hemiptera: Heteroptera: Pentatomomorpha: Pentatomoidea: Thaumastellidae) are reviewed. In addition a fourth, undescribed species is reported from South Africa (Western Cape). Thaumastella aradoides Horváth, 1896, is recorded for the first time from Egypt, Oman, Saudi Arabia, United Arab Emirates, and the states of Khartoum and Sennar in Sudan. Additional records of Thaumastella namaquensis Schaefer & Wilcox, 1971, from Namibia (Hardap, ||Kharas) and South Africa (Northern Cape), as well as information on habitat of Thaumastella namaquensis and Thaumastella elizabethae Jacobs, 1989, are provided. Photographs of the holotypes of the three already described species and their labels are also presented. The distribution of all four species is mapped.